The Form of Ideology and the Ideology of Form : Cold War, Decolonization and Third World Print Cultures. - Orsini, Francesca; Srivastava, Neelam; Zecchini, Laetitia (Cambridge, UK : Open Book Publishers, 2022)
This timely volume focuses on the period of decolonization and the Cold War as the backdrop to the emergence of new and diverse literary aesthetics that accompanied anti-imperialist commitments and Afro-Asian solidarity. Competing internationalist frameworks produced a flurry of writings that made Asian, African and other world literatures visible to each other for the first time. The book's essays examine a host of print culture formats (magazines, newspapers, manifestos, conference proceedings, ephemera, etc.) and modes of cultural mediation and transnational exchange that enabled the construction of a variously inflected Third-World culture which played a determining role throughout the Cold War.
Intro -- Contents -- Acknowledgements -- List of Illustrations -- Notes on Contributors -- Note on Transliteration -- Introduction -- 1. The Traveller as Internationalist: Syed Mujtaba Ali -- 2. Writing Friendship: The Fraternal Travelogue and China-India Cultural Diplomacy in the 1950s -- 3. Literary Activism: Hindi Magazines, the Short Story and the World -- 4. Publishing the Resistance: Third-Worldist Writing in Cold War Italy -- 5. The Meanings, Forms and Exercise of 'Freedom': The Indian PEN and the Indian Committee for Cultural Freedom (1930s-1960s) -- 6. Moroccan Intellectuals Between Decolonization and the Arab Cold War: Abdallah Laroui's Critical and Literary Writing -- 7. The Poetics and Politics of Solidarity: Barg el-Lil (1961) and Afrotopia -- 8. Euforia, Desencanto: Roberto Bolaño and Barcelona Publishing in the Transition to Democracy -- Afterword: A World of Print -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Transmission of texts--History--20th century; Electronic books